2020
DOI: 10.3390/cli8030039
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Climate Change in World Heritage Properties: Evaluating Landscape-Based Approach in the State of Conservation System

Abstract: Climate change is increasingly being recognized as a threat to natural and cultural World Heritage (WH) sites worldwide. Through its interaction with other stressors, climate change accelerates existing risks while also creating new obstacles. A more considerable focus is needed in both research and practice to explore proactive measures for combatting this issue (e.g., mitigation and actions prior to impacts occurring). World Heritage values in climate change decision-making processes is an important factor i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 67 publications
(81 reference statements)
0
22
0
Order By: Relevance
“…All sites are subject to landscape evolution and to a range of pressures, such as climate change, encroachment, and invasive species. Managers need a better understanding of how malleable heritage values are, what forces change them and the significance of those changes (9). As site conditions change, the attributes that supported the listing (e.g., the OUV if it is a World Heritage site) may be lost.…”
Section: Heritage Is Commonly Managed As a Static Resourcementioning
confidence: 99%
See 1 more Smart Citation
“…All sites are subject to landscape evolution and to a range of pressures, such as climate change, encroachment, and invasive species. Managers need a better understanding of how malleable heritage values are, what forces change them and the significance of those changes (9). As site conditions change, the attributes that supported the listing (e.g., the OUV if it is a World Heritage site) may be lost.…”
Section: Heritage Is Commonly Managed As a Static Resourcementioning
confidence: 99%
“…Managers must look to the future and frame both reactive and proactive strategies. Recent work (19,20,21) has shown that currently, most responses are reactive, attempting to replace lost values rather than being proactive about potential future values (9,22). Proactive management will look to the future, assess the risks to the values of the site and adapt their management accordingly.…”
Section: Heritage Is Commonly Managed As a Static Resourcementioning
confidence: 99%
“…The prevalence of climate change impact monitoring at heritage sites is increasing, particularly at natural heritage sites within the WH system (Guzman et al 2020). Additionally, researchers are documenting the constraints associated with adapting heritage sites to changing climatic conditions (Fatorić & Seekamp 2017b;Sesana et al 2018), as well as providing decision guidance by assessing the vulnerability of heritage sites (e.g., Reeder-Meyers 2015; Reiman et al 2018), measuring the significance of heritage sites (e.g., Fatorić & Seekamp 2018; Mendes Zancheti & Tone Ferreira Hidaka 2011), or integrating both (e.g., Carmichael et al 2018;Heilen et al 2018;Xiao et al 2019).…”
Section: Adaptation Of Heritagementioning
confidence: 99%
“…For example, Perry (2011) identified the most at-risk natural World Heritage (WH) sites, and Marzeion and Levermann (2014) assessed coastal cultural WH sites vulnerable to sea level rise. Most recently, Guzman et al (2020) documented the increasing prevalence of climate change as a threat within the WH monitoring system (i.e., State of Conservation (SOC) reports). Simultaneously, there has been an emerging trend within critical heritage studies to critique climate change concerns for heritage only in relation to tangible, physical resource (and the patriarchal policies that designated that heritage), rather than the active and dynamic role of heritage values that provide meaning and are manifested in tangible attributes (DeSilvey 2017; Krauß 2015;Lafrenz Samuels 2018).…”
Section: Introductionmentioning
confidence: 99%
“…At an international level, constant efforts are made to detect (Tapete and Cigna, 2019), monitor (Agapiou et al, 2020), and assess (Nicu, 2016) mass wasting processes for cultural heritage management. Other efforts are aimed towards the improvement of adaptation measures (Guzman et al, 2020), sustainable development (Guo et al, 2019) and valorisation (Lorusso et al, 2018) of cultural heritage resources. Among surface processes, landslides (Jiao et al, 2019) and gully erosion can damage or even destroy cultural heritage sites.…”
Section: Introductionmentioning
confidence: 99%